2003
DOI: 10.1021/es020838h
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Spectroscopic Studies of the High Temperature Reduction of Cu(II)O by 2-Chlorophenol on a Simulated Fly Ash Surface

Abstract: The reaction of 2-chlorophenol on Cu(II)O at 375 degrees C is studied using X-ray absorption near edge structure (XANES) spectroscopy. A mixture of copper(II) oxide and silica is prepared to serve as a surrogate for fly ash in combustion systems. 2-Chlorophenol is utilized as a model precursor for formation of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/F). The Cu K-edge spectra shiftto lower binding energy, reflecting the reduction of the copper. The substrate is found to form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 36 publications
4
52
0
Order By: Relevance
“…We have previously demonstrated that 2-MCP interacts with the surfaces of metal oxides through a chemisorption mechanism (Farquar et al, 2003; Lomnicki and Dellinger, 2003a; Vejerano et al, 2011). Two pathways of chemisorption have been proposed for chlorophenols: i) elimination of H 2 O (upper path in Scheme 1) and ii) elimination of both H 2 O and HCl (lower path Scheme 1) (Lomnicki et al, 2008; Nganai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that 2-MCP interacts with the surfaces of metal oxides through a chemisorption mechanism (Farquar et al, 2003; Lomnicki and Dellinger, 2003a; Vejerano et al, 2011). Two pathways of chemisorption have been proposed for chlorophenols: i) elimination of H 2 O (upper path in Scheme 1) and ii) elimination of both H 2 O and HCl (lower path Scheme 1) (Lomnicki et al, 2008; Nganai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these radicals are resonance stabilized and can exist as primarily oxygen-centered or carbon-centered mesomers (cf. Scheme 1 Species II and III) (Farquar et al, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…This could be induced by a competitive reaction between the absorbed species and a gas-phase molecule (Farquar et al 2003;Lomnicki and Dellinger 2003a). The surfaceassociated chlorophenoxyl can react with gas-phase chlorobenzenes to form PCDEs, with another vicinal chlorophenoxyl via a Langmuir-Hinshelwood pathway to form PCDF, and with gas-phase polychlorophenol via an EleyRideal pathway to form PCDD.…”
Section: The Trend and Relationship Between Pcdes And Pcdfsmentioning
confidence: 99%
“…EPFR-containing PM has been demonstrated to produce pulmonary and cardiovascular dysfunction in animal models, with greater toxicity than non-EPFR-containing PM 511 . EPFRs were first proposed to form through the reduction of metal oxides by high-temperature exposure (above 150°C) to simple substituted aromatics, which electron and X-ray spectroscopy has shown to occur on CuO 12,13 and TiO 2 14 model systems. However, the longest-lived EPFR species observed to date are phenoxy radicals generated on ZnO 15 , which presents a significant challenge to the generic model of EPFR formation because it is usually not possible to create a Zn(I) oxidation state except under rare conditions 1620 .…”
Section: Introductionmentioning
confidence: 99%